The effect of self-disclosure on mass trust through TikTok: An empirical study of short video streaming application users - Ruangkanjanases, Athapol; Sivarak, Ornlatcha; Jong, Din; Zhou, Yajun (Frontiers in Psychology, 2022)
In the short video application scenario, self-disclosure helps to establish and maintain relation-ships with others, and is important for the formation of mass trust. To this end, this study inves-tigates the impact of self-disclosure on mass trust in the context of short video applications based on social exchange theory, and introduces perceived similarity to explain the specific impact mechanism while focusing on the boundary conditions of trust disposition in it. This study takes Tik Tok as the research object and analyzes the data obtained from the questionnaire survey. The empirical test results show that self-disclosure not only affects mass trust directly, but also indi-rectly through perceived similarity. In addition, a moderating effect of trust disposition on per-ceived similarity was found to affect mass trust. Finally, this study discusses the theoretical con-tributions, practical implications, and future perspectives of self-disclosure on mass trust.